The Effect of Leonardite on Chromium Toxicity and Growth of Cordes Rose - Ayşen Akay; Mohammed Yashar Omar (Turkish Journal of Agriculture: Food Science and Technology, 2022)
High concentrations of chromium in the soil have a toxic effect on the living organisms in the soil ecosystem. If chromium, which is not an absolute essential element, accumulates in plants, it causes structural changes, causing a decrease in plant growth and also high toxicity due to its accumulation in biomass. Use of plants to remove chromium (Cr) from contaminated soils, it is an environmentally efficient, cost-effective, modern, applicable technique. The different species of plant and ornamental plants are used in this technique. In this study, the Kordes shrub rose used in landscaping in our province, Cr phytoremediation capacity was evaluated by growing at contaminated soil with Cr. In the study, the different doses of Cr (0, 50, 100, 500, 1000 mg kg-1) have been applied in Cr+3 and Cr+6 forms. In addition, two doses (0% and 3%) of leonardite were added to the pots to determine the effect on the developmental status of the plants and Cr uptake. In the study, plant height, number of branches, number of flowers, flower diameter, stem diameter, flower yield values and total wet and dry weight values at the end of the experiment were determined. At the end of the experiment, it was observed that generally developmental status of the plants was adversely affected at high Cr doses. Especially at 500 and 1000 mg kg-1 application doses was observed that the plants could not withstand Cr toxicity in a short time. It has been observed that plants treated with leonardite were healthier than those without. According to the data obtained at the end of the study, it was determined that the resistance of plant to high doses of Cr was low, but it showed better growth at 50 and 100 mg kg-1 doses.